Efficacy and safety of Duhuo Jisheng Decoction add-on bisphosphonate medications in patients with osteoporosis: A meta-analysis of randomized controlled trials. (30th January 2022) - Huang, Chung-Yu; Cheng, Ciao-Jhih; Chiou, Wen-Fei; Chang, Wei-Chiao; Kang, Yi-No; Lee, Mei-Hsien
Abstract: Ethnopharmacological relevance: Duhuo Jisheng Decoction (DHJSD) is the most frequently prescribed herbal formula for the treatment of osteoporosis. However, efficacy and safety of DHJSD add-on bisphosphonate medications remain unclear. Aim of the study: The purpose of this study was to reveal efficacy and safety of DHJSD add-on bisphosphonate medications in patients with osteoporosis through a systematic review with meta-analysis of randomized controlled trials (RCTs). Methods: Five important databases were searched for RCTs on this topic, and two authors individually extracted information and data concerning study design, baseline characteristics, efficacy rate, bone mineral density (BMD), pain score, and adverse event. Meta-analysis was done mainly with risk ratio (RR) and standardized mean difference (SMD) for BMD and pain, using random-effects model; while Peto odds ratios (PORs) were used for pooling adverse event rates due to sparse data. Point estimate was reported with 95% confidence intervals (CIs). Results: Seventeen RCTs (n = 1526) met eligibility criteria, and were included in this synthesis. Pooled estimates demonstrated that as compared with no DHJSD, DHJSD-B led to significantly higher efficacy rates (RR = 1.25, 95%CI: 1.19–1.31; I 2 = 0%), more lumbar BMD (SMD = 0.61, 95%CI: 0.25–0.96; I 2 = 20%), lower pain score (SMD = −1.10, 95%CI: 1.40–0.79; I 2 = 33%), and lower overall adverse event rates (POR = 0.40; 95%CI: 0.20–0.97; I 2 = 27%). Conclusion: Adding DHJSD on bisphosphonate medications seems to be an effective and safe strategy in treating patients with osteoporosis. Graphical abstract: Image 1 Highlights: DHJSD group significantly improved BMD within six months follow-up. DHJSD group had significantly lower pain score at three-month follow-up. DHJSD group had significantly lower rates of overall adverse event.